2007
DOI: 10.1103/physrevlett.99.127002
|View full text |Cite
|
Sign up to set email alerts
|

Odd Triplet Pairing in Clean Superconductor/Ferromagnet Heterostructures

Abstract: We study triplet pairing correlations in clean Ferromagnet (F)/Superconductor (S) nanojunctions, via fully self consistent solution of the Bogoliubov-de Gennes equations. We consider FSF trilayers, with S being an s-wave superconductor, and an arbitrary angle α between the magnetizations of the two F layers. We find that contrary to some previous expectations, triplet correlations, odd in time, are induced in both the S and F layers in the clean limit. We investigate their behavior as a function of time, posit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
144
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(148 citation statements)
references
References 25 publications
4
144
0
Order By: Relevance
“…26,35,38,39. Over the last couple of years, induction of triplet-correlations in layered heterostructures with ferromagnets (F) and superconductors (S) in the clean limit has been studied by using different formalisms and configurations in Refs. [40][41][42]. On the experimental side, Keizer et al 44 observed a long-range supercurrent through half-metallic CrO 2 , whereas very recent work also reports observation of a long-range supercurrent through an inhomogeneous magnetic layer 6,27 .…”
Section: Introductionmentioning
confidence: 95%
“…26,35,38,39. Over the last couple of years, induction of triplet-correlations in layered heterostructures with ferromagnets (F) and superconductors (S) in the clean limit has been studied by using different formalisms and configurations in Refs. [40][41][42]. On the experimental side, Keizer et al 44 observed a long-range supercurrent through half-metallic CrO 2 , whereas very recent work also reports observation of a long-range supercurrent through an inhomogeneous magnetic layer 6,27 .…”
Section: Introductionmentioning
confidence: 95%
“…Until both better theoretical models and more varied experimental observations are made available, one cannot conclusively say that there is indeed an induced triplet state in these systems, but at this point the facts fit this explanation and no better one has been proposed. 17 Many theoretical studies agree that it is possible to induce this exotic state in certain SF systems 17,18,19,20,21,22,23,24,25,26,27,28,29 (perhaps even in the nonmagnetic 30 case) with ordinary singlet pairing in S. Some studies use an SFF ′ S arrangement in which the F and F ′ layers have different magnetization orientations. Others assume that a domain structure in a single F layer is responsible for the symmetry breaking.…”
Section: Introductionmentioning
confidence: 99%
“…28 To understand and probe the underlying triplet state, investigations have been done on conductance spectra in simpler FS structures 31 with arbitrary magnetization alignment and with spin active interfaces, as well as in diffusive 29 SF junctions, through characterizing the possible superconductor symmetry classes consistent with Pauli's principle. With the exception of our early work 18 on SFS trilayers and some recent work on SFS Josephson junctions, 28 the studies above are done in the dirty limit through linearized Usadel-type or other quasiclassical equations. The disadvantage of a quasiclassical approach is that it is unsuitable for magnets with an exchange field on the order of the Fermi energy.…”
Section: Introductionmentioning
confidence: 99%
“…As a result a nonzero Josephson current flows through the strong ferromagnets (such as half metals) [33,34,35]. The triplet correlations also penetrate into the superconductors however their amplitudes are small in comparison to the bulk singlet component [36]. The triplet correlations are also generated by magnetization dynamics such as spin precession and magnonic excitations.…”
Section: Josephson Currentmentioning
confidence: 99%